The European Parliament’s Proposal for an EU State of Emergency Clause: A Comparative and Constitutional Analysis - Guido Bellenghi (Croatian Yearbook of European Law and Policy)
Following the Conference on the Future of Europe, the European Parliament presented a proposal to reform the Treaties, aiming to expand the competences of the EU in emergency contexts and enhance parliamentary participation in the adoption of emergency measures. Notably, the Parliament suggests introducing a new state of emergency clause, modelled on similar provisions included in national emergency laws. This proposal reveals several issues associated with the attempt of transposing the conceptual categories and legal schemes of national emergency law into EU law. Drawing from examples of EU Member States’ emergency laws, this article analyses these issues from a comparative perspective, focusing on the equilibrium between the recognition of extraordinary powers and the construction of appropriate constitutional safeguards. Furthermore, it critically assesses the proposal’s potential implications for EU constitutional law, discussing in particular the trajectory of EU integration, the role of the adjudicature, and the constitutional design of EU competence.